PENINGKATAN BERPIKIR KRITIS SISWA SEKOLAH DASAR DENGAN MENERAPKAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA LEMPAR KARET PENGETAHUAN - Dwi Hesti Lilis Setyawati; Fina Fakhriyah; Khamdun Khamdun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2020)
This research was conducted to describe the improvement of students' critical thinking skills by applying the Contextual Teaching and Learning learning model aided by the Media Rubber Throwing media. The research carried out included classroom action research with the research subjects of class IV students totaling 19 students. Data collection techniques in this study are tests and non-tests, data analysis used that the researcher used in this study is qualitative and quantitative data. The results showed that is increases the students' critical thinking skills. This is evidenced by the average percentage at the pre-cycle stage obtained a percentage of 52.8% with the criteria for guidance. In cycle 1 it increased to 70.39% with the sufficient criteria, and on the second cycle increases to 82.5% with a good criteria. Based of the results of this study, the researcher conclude that through the application of the Contextual Teaching and Learning model assisted by the Throwing Rubber Knowledge media can improve students' critical thinking skills on theme 6 of my ideals in grade IV SD 2 Tenggeles.